Homosexual Pairing within a Swarm-Based Mating System: The Case of the Chironomid Midge - Athol J. McLachlan (Psyche: A Journal of Entomology)
Homosexuality has been dubbed the Darwinian paradox, because it raises the question of how behaviour that would seem to reduce the chance of successful mating can be maintained by natural selection. This question rests on the assumption that same sex mating is the result of active choice of partner, hardwired into the mating behaviour, but there is an alternative explanation for such behaviour. I refer to the possibility that same-sex mating is the result, not of adaptive behaviour at all, but rather of errors due to imprecise sensory machinery. Such an explanation finds support within the mating system of insects with swarm-based mating systems. To explore this case, I turn to the common chironomid midge. I show that homosexual pairing here, exclusively involving male/male pairs, is common. I attempt to show that this observation, together with data on insect predators of swarming midges, can be used to penetrate the mysteries of this fascinating but elusive mating system.